2012
DOI: 10.1029/2011jd017105
|View full text |Cite
|
Sign up to set email alerts
|

Luminous pulses during triggered lightning

Abstract: [1] A triggered lightning flash that transferred negative charge to ground in central New Mexico produced more than three levels of branching above the main channel to ground in a 1 km vertical field of view. A high-speed video recording shows that the main channel had about 50 brief luminous pulses, many of which were superimposed on a slowly changing persistent luminosity. In contrast, superposition was rare in the uppermost visible branches because luminous pulses first appeared on preexisting dark channels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 14 publications
3
22
0
Order By: Relevance
“…Here, combined with the observations by different authors [e.g., Shao et al ., ; Rakov et al ., ; Mazur and Ruhnke , ; Yoshida et al ., ], we agree with Winn et al . [] on the issue of the generation (or origin process) of M‐component. Nonetheless, it should also be emphasized that the modes of charge transfer by M‐component and dart leader‐return stroke are different, mainly concerning the findings in triggered lightning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, combined with the observations by different authors [e.g., Shao et al ., ; Rakov et al ., ; Mazur and Ruhnke , ; Yoshida et al ., ], we agree with Winn et al . [] on the issue of the generation (or origin process) of M‐component. Nonetheless, it should also be emphasized that the modes of charge transfer by M‐component and dart leader‐return stroke are different, mainly concerning the findings in triggered lightning.…”
Section: Discussionmentioning
confidence: 99%
“…For the issue on whether there is a responsive wave propagating upward when the downward wave reaches the ground, an affirmative reply is obtained with responding to the boundary condition, as also mentioned by Winn et al . []. Meanwhile, the simulation conducted with the assumption that there is not any responsive upward wave exhibits unacceptable disagreement between the modeled E‐field and the measured E‐field (as also discussed by Rakov et al .…”
Section: Mechanism Of M‐componentmentioning
confidence: 96%
“…For upward positive triggers, there is no negative breakdown to contend with, allowing the positive breakdown to be better studied than in natural lightning. The flash was observed by a three-dimensional Lightning Mapping Array (LMA) [Rison et al, 1999;Thomas et al, 2004] and by high-speed video [Winn et al, 2012], which revealed a highly branched structure inside the parent storm. Edens et al [2012] present detailed observations of the positive and negative breakdown processes during a triggered-CG flash at Langmuir Laboratory in New Mexico.…”
Section: Introductionmentioning
confidence: 99%
“…We have not included failed dart leaders in this analysis, although there are many cases (particularly those that we would categorize as type B) in our data set. According to our categorization, the two branched dart leaders shown in Schonland et al [1938] are apparently Type "A" and Type "B then stepped," while the example shown in Winn et al [2012] is Type "A." 3.3.1.…”
Section: Physical Characteristicsmentioning
confidence: 99%
“…Winn et al [2012] report on a triggered flash in which three 100 m "spurs" (or dart leader branches) are visible as a dart leader passes the junctions of former branches, and these "spurs" illuminate during the subsequent RS. Stolzenburg et al [2013a] studied three CG flashes in which a stepped leader intercepts a former channel and changes to a dart leader; these events were studied with video data collected at 50,000 frames per second and with an array of E-change sensors.…”
Section: Introductionmentioning
confidence: 99%